Fibronectin binding proteins are required for biofilm formation by community-associated methicillin resistant Staphylococcus aureus strain LAC - GEOGHEGAN, JOAN (My University, 2014)
Community-associated methicillin-resistant Staphylococcus aureus of the USA300 lineage is emerging as an important cause of medical device-related infection. However, few factors required for biofilm accumulation by USA300 strains have been identified, and the processes involved are poorly understood. Here, we identify S. aureus proteins required for the USA300 isolate LAC to form biofilm. A mutant with a deletion of the fnbA and fnbB genes did not express the fibronectin-binding proteins FnBPA and FnBPB and lacked the ability to adhere to fibronectin or to form biofilm. Biofilm formation by the mutant LAC∆fnbAfnbB could be restored by expression of FnBPA or FnBPB from a plasmid demonstrating that both of these proteins can mediate biofilm formation when expressed by LAC. Expression of FnBPA and FnBPB increased bacterial aggregation suggesting that fibronectin-binding proteins can promote the accumulation phase of biofilm. Loss of fibronectin-binding proteins reduced the initial adherence of bacteria, indicating that these proteins are also involved in primary attachment. In summary, these findings improve our understanding of biofilm formation by the USA300 strain LAC by demonstrating that the fibronectin-binding proteins are required.
PUBLISHED
Keywords: Staphylococcus aureus; Genes & Society; Immunology, Inflammation & Infection; BACTERIAL BIOFILMS; BIOFILM; BIOFILM FORMATION; METHICILLIN-RESISTANT STAPHYLOCOCCUS AUREUS; Microbiology; STAPHYLOCOCCUS AUREUS